Effects of Recovery-Orientation on the Use of Forced Medication and Maximum Daily Drug Dose: The “Weddinger Modell” - Czernin, Klara; Bermpohl, Felix; Wullschleger, Alexandre; Mahler, Lieselotte (Frontiers in Psychiatry, 2021)
Objective: The aim of the present study was to analyze the effects of the implementation of the Recovery-orientated psychiatric care concept „Weddinger Modell“ on the incidence of forced medication, the total number of forced medication incidents per affected case, the maximum dose of a singular forced medication and the maximum voluntary daily drug dose of different psychotropic drugs administered during an inpatient stay. Methods: This retrospective case-control study included 234 patients. A pre/post comparison of patients on two acute psychiatric wards before (control group, n=112) and after (intervention group, n=122) the implementation of the Weddinger Modell in 2010 was performed. Patient data was selected at two reporting periods before and at two reporting periods after 2010. Results: No significant differences were found in the incidence of forced medication and the total number of forced medications. A significant reduction of the maximum forced medication dose of haloperidol in the intervention group was seen. Furthermore, the analysis of the intervention group showed a significant reduction of the maximum voluntary daily drug doses of clozapine, haloperidol and risperidone. Discussion: The results indicate that the implementation of the Weddinger Modell had no effect on the incidence of forced medication, but it can help to improve the approach to psychotropic drugs. Despite the reduction of mechanical coercive measures by the model, as shown in a previous study, there is no increase in forced medications or administered drug doses. Focus on Recovery helps in reducing coercion in acute psychiatric care.